Evaluation of the potential therapeutic benefits of macrophage reprogramming in multiple myeloma - Gutiérrez González, Alejandra; Martínez Moreno, Mónica; Samaniego, Rafael; Arellano Sánchez, Noemí; Salinas Muñoz, Laura; Relloso, Miguel; Valeri, Antonio; Martínez López, Joaquín; Corbí, Angel L.; Hidalgo, Andrés; García Pardo, Ángeles; Teixidó, Joaquín; et al. (My University, 2024)
Tumor-associated macrophages (TAM) are important components of the multiple myeloma (MM) microenvironment that support malignant plasma cell survival and resistance to therapy. It has been proposed that macrophages (MØ) retain the capacity to change in response to stimuli that can restore their antitumor functions. Here, we investigated several approaches to reprogram MØ as a novel therapeutic strategy in MM. First, we found tumor-limiting and tumor-supporting capabilities for monocyte-derived M1-like MØ and M2-like MØ, respectively, when mixed with MM cells, both in vitro and in vivo. Multicolor confocal microscopy revealed that MM-associated MØ displayed a predominant M2-like phenotype in the bone marrow of MM patient samples, and a high expression of the pro-M2 cytokine macrophage migration inhibitory factor (MIF). To reprogram the protumoral M2-like MØ present in MM toward antitumoral M1-like MØ, we tested the pro-M1 cytokine granulocyte¿macrophage colony-stimulating factor (GM-CSF) plus blockade of the M2 cytokines macrophage colony-stimulating factor or MIF. The combination of GM-CSF plus the MIF inhibitor 4-iodo-6-phenyl-pyrimidine achieved the best reprogramming responses toward an M1 profile, at both gene and protein expression levels, as well as remarkable tumoricidal effects. Furthermore, this combined treatment elicited MØ-dependent therapeutic responses in MM xenograft mousemodels, which were linked to upregulation of M1 and reciprocal downregulation of M2 MØ markers. Our results reveal the therapeutic potential of reprogramming MØ in the context of MM. (Blood. 2016;128(18):2241-2252)